Z-type shear connector for interface of hollow-core slab and cast-in-place topping concrete. (1st July 2020) - Yuksel, E.; Gullu, A.; Durgun, Y.; Binbir, E.; Senol, E.; Khajehdehi, A.; Saruhan, H.
Highlights: Z-type shear connectors are cost effective and easy applicable for the interface. Three dissimilar interface conditions were studied experimentally. Full scale push-off loading tests were applied to investigate the behaviour. It is proposed an alteration for the interface shear capacity equation of ACI 318M. Abstract: Precast hollow-core slabs ( PHSs ) are widely used in precast construction due to their relatively low dead weight and easy assemblage. Cast-in-place topping concrete ( TC ) is utilized to obtain composite sections and to enhance in-plane stiffness of the slab system. Shear transfer between the layers of a composite slab can be provided by the upper face roughness of PHS . However, the roughening process may not be preferred in some plants. This paper evaluates the efficiency of Z-type shear connectors applied in the interface between PHS and TC . Three dissimilar interface conditions (i.e., Z-reinforced, smooth and rough) were studied experimentally in full-scale specimens. Push-off loading was applied to evaluate the interface shear transfer capability of the specimens, and Z-type shear connectors were found to be the most effective when they are applied at each joint between PHSs . The achievements of some code equations to assess interface shear strength were also investigated, and an alteration for the interface shear capacity equation of ACI 318M is proposed.